Solar DER Investment for MWANI Qatar Building at Hamad Port - Karama, Adel (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This document discusses the benefits of adding a solar distributed energy resource (DER) investment to MWANI Qatar (MQ) building at Hamad Port. The social and environmental aspects of a Solar PV system with battery storage were evaluated besides economic calculations outcome. The calculations show a marvelous 96% CO2 emission reduction with significant battery storage benefits and a 269,676 KWh/yr reduction in electricity leading to a $33,217.52 annual savings. In essence, the State of Qatar is governed by a vision of excellence, innovation and leadership that this investment could be a role model for the country's sustainable future developments.